Dirasah Ma Ba’da al-Waqi’ah Laday Thullab al-Shaf al-Tsanawiy ‘An Uslub al-Muhakah li Tarqiyyah Isti’ab al-Mufradat - Rozaanah, Rozaanah; Riyadi, Slamet; Fikri, Hidayatul (Universitas Muhammadiyah Sumatera Barat, 2022)
The purpose of this study was to know the student's Arabic vocabulary mastery in the class that did not use simulation methods and classes that used simulation methods, and to what degree the effectiveness of the methods used to increase student's Arabic vocabulary mastery of the XI class in Pondok Pesantren Modern Ta 'dib al-Syakirin, Medan Johor. The research method used is an ex post facto quantitative study method. The results of this study indicate that for mastery of the student's Arabic vocabulary when not using the practice of simulation are obtained with an average of 64.72, where 4 students are